Preservation of metabolic flexibility in skeletal muscle by a combined use of n-3 PUFA and rosiglitazone in dietary obese mice - Horakova, Olga; Medrikova, Dasa; van Schothorst, Evert M; Bunschoten, Annelies; Flachs, Pavel; Kus, Vladimir; Kuda, Ondrej; Bardova, Kristina; Janovska, Petra; Hensler, Michal; Rossmeisl, Martin; Wang-Sattler, Rui; et al. (PloS one, 2012)
Insulin resistance, the key defect in type 2 diabetes (T2D), is associated with a low capacity to adapt fuel oxidation to fuel availability, i.e., metabolic inflexibility. This, in turn, contributes to a further damage of insulin signaling. Effectiveness of T2D treatment depends in large part on the improvement of insulin sensitivity and metabolic adaptability of the muscle, the main site of whole-body glucose utilization. We have shown previously in mice fed an obesogenic high-fat diet that a combined use of n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) and thiazolidinediones (TZDs), anti-diabetic drugs, preserved metabolic health and synergistically improved muscle insulin sensitivity. We investigated here whether n-3 LC-PUFA could elicit additive beneficial effects on metabolic flexibility when combined with a TZD drug rosiglitazone. Adult male C57BL/6N mice were fed an obesogenic corn oil-based high-fat diet (cHF) for 8 weeks, or randomly assigned to various interventions: cHF with n-3 LC-PUFA concentrate replacing 15% of dietary lipids (cHF+F), cHF with 10 mg rosiglitazone/kg diet (cHF+ROSI), cHF+F+ROSI, or chow-fed. Indirect calorimetry demonstrated superior preservation of metabolic flexibility to carbohydrates in response to the combined intervention. Metabolomic and gene expression analyses in the muscle suggested distinct and complementary effects of the interventions, with n-3 LC-PUFA supporting complete oxidation of fatty acids in mitochondria and the combination with n-3 LC-PUFA and rosiglitazone augmenting insulin sensitivity by the modulation of branched-chain amino acid metabolism. These beneficial metabolic effects were associated with the activation of the switch between glycolytic and oxidative muscle fibers, especially in the cHF+F+ROSI mice. Our results further support the idea that the combined use of n-3 LC-PUFA and TZDs could improve the efficacy of the therapy of obese and diabetic patients.
Keywords: kosterní svaly; myši; Mice, Inbred C57BL; mužské pohlaví; Diet, High-Fat; Muscle Fibers, Skeletal; thiazolidindiony; Male; Thiazolidinediones; synergismus léků; regulace genové exprese; dieta s vysokým obsahem tuků; glykolýza; kosterní svalová vlákna; Metabolomics; rosiglitazon; obezita; Obesity; myši inbrední C57BL; Fatty Acids, Omega-3; Glycolysis; Animals; Mice; metabolomika; zvířata; Drug Synergism; Oxidation-Reduction; Muscle, Skeletal; oxidace-redukce; Rosiglitazone; Gene Expression Regulation; omega-3 mastné kyseliny